PERANAN PEMUKA PENDAPAT DALAM ADOPSI INOVASI TEKNOLOGI BARU 145 - 152 PADA PETANI DI KABUPATEN KULON PROGO - Larisu, M. Adlan (Jurnal Ilmu-Ilmu Pertanian, 2005)
The purpose of this research is to know and understand the role of opinion leader toward farmers in adopting and innovating technology Kulon Progo district and also to know the characteristic of opinion leader as well as farmers and to influenced factor For Examining characteristic of opinion leader and farmer as well in adopting and innovating technology application was used test. With the result that in average the opinion leaders were older, have higher education, level and they have larger of land holding than ordinary farmers to Examining the influenced factors to ward adoption inovation of urea tablet was used regression Correlation analysis and the result of it has shown that there were two factors which influenced were the land size and the role of neighbour .The role of opinion leader didnt influence toward adoption inovation of technology, application due to information flow of agriculture inovation itself was indirectly dispersed from the opinion leader to the farmer, but information flow was running a way through many steps, one of them was trough the neighbour